Pengaruh Gadget terhadap Kesehatan Mental Anak - Hasanah, Muhimmatul (Indonesian Journal of Islamic Early Childhood Education, 2017)
Mental health of children is a mental condition of children who do not experience mental illness, and the ability to think clearly, control emotions, and socialize with children his age. Mental health is less good in childhood can lead to more serious behavior disorders due to mental imbalance and emotional, and social life of children who are less good. One reason could be due to excessive use of gadgets. It can not be denied that the gadget has a positive or negative impact on the childs development. The positive effects such as gadgets can stimulate the senses of sight and hearing. Negative effects of gadgets on children include the brain growth is too fast, developmental obstacles, obesity, sleep disorders, mental illness, aggressive, dementia digital, addiction, radiation and not sustainable.